From the London Conference to the London Secret Pact: The Policy Followed by Italy Towards Albania - Ibra, Dashnor (Mediterranean Journal of Social Sciences, 2012)
The purpose of this paper is the analytical representation of the historical framework, political and diplomatic policy that hasaccompanied the Italian towards Albania during the years 1912-1915.The paper should be understood as an intention to give a fullinterpretation of a given historical period, the first in a particular context, the policy followed by Italy towards Albania.This will be achievedthrough an analysis that is intended to be deployed in an organic way of important documents and to better understand the broad policyframework of that time.The period from 1912-1915 coincides with the acquisition of independence of Albania and where Italy stood as abalance to the power of the Austro-Hungarian. During this period the Italian politics ranged between two poles, one side of the partitionof the Albanian territories and from the other side for its independence, but always with a higher interest rate, to influence or to protectthe small country of Albania.